The modern Dental Cast Reference Collection from the University of Coimbra, Portugal - Silva, Ana Maria (2022)
Introduction Identified skeletal and skull collections are centrepiece for research in biological anthropology. However, until recently, the same relevance has not been placed on dental cast collections. This perspective evolved, mainly, with the research on population variation and human identification through dental characteristics. While dental collections exist throughout the world, their reports and documentation are scarce in the literature. Aims This work aims to present the new Dental Cast Reference Collection – University of Coimbra (DCRC - UC) housed in the Laboratory of Prehistory of the Department of Life Sciences of the University of Coimbra (Portugal). Basic procedures The modern dental cast collection (DCRC - UC) was created in 2016 for teaching and research purposes. The casts were obtained from volunteers who answered a brief questionnaire (sex, age, nationality, previous orthodontic and dental data) after informed consent. Main findings The collection includes the dental casts of 90 adult individuals of both sexes: 69 females and 21 males. The volunteers were students, teachers and visiting researchers of the Department of Life Sciences of the University of Coimbra. Age ranges from 17 to 49 years, including individuals of Portuguese (n = 79) and non-Portuguese nationality (n = 11). Lastly, the strategy of the conservation and storage conditions of the casts are underlined, a vital aspect of this working collection, emphasizing its protection while also allowing it to function as a usable resource. Principal conclusions Currently, the addition of new individuals to the dental cast collection is paused due to the COVID-19 pandemic, however the future work and expected expansion will require new logistic solutions. The DCRC – UC is an invaluable resource to both research and teaching activities.